STUDI PERBANDINGAN PERILAKU DAN KINERJA STRUKTUR BAJA MENGGUNAKAN KOLOM KOMPOSIT CONCRETE ENCASED DAN CONCRETE FILLED TUBE, SERTA NON KOMPOSIT - I Ketut Diartama Kubon Tubuh; Made Sukrawa; I Gede Adi Susila (JURNAL SPEKTRAN, 2017)
Comparative study of steel structure behavior and performance using composite and non composite columns were done by making five structure models. A model using wide flange steel columns, two models with circular and square concrete encased columns (MCEC and MCES), also two models with circular and square concrete filled tube columns (MCFTC and MCFTS). Columns on 4th-5th floor are smaller than columns on three floors below. Structure behavior were observed through elastic analysis which are displacement and interstory drift. While structure performance were evaluated through non linear static Pushover analysis using SAP2000®. The analysis showed that with P-M ratio ranging from 0.79 until 0.88, all models interstory drifts were exceed limit on 1st, 2nd and 4th floors. Countermeasures were done by rotating half of total MS steel columns (then became MS-R), enlarging 4th-5th floor columns on MS-R and MCFTC, and also installing eight X-bracings on all models ground floor. Pushover analysis showed that performance level of all models are Immediate Occupancy (IO) except MCFTS. MCFTS model which in Collapse (C) performance level were improved by increasing thickness of steel section (then became MCFTS-Improved) and resulting IO performance level. Calculation of structure materials cost showed the most expensive until the cheapest models respectively were MS-R, MCFTS-Improved, MCEC, MCES, and MCFTC with comparison 1:0,99:0,88:0,87:0,86. Keywords: concrete encased (CE), concrete filled tube (CFT), X-bracing, Pushover analysis